THE FRESHMEN’S ABILITY ON USING THE GRAMMAR OF ENGLISH IN ACADEMIC YEAR 2019/2020 - Lumban Raja, Viator (Kairos English Language Teaching Journal, 2021)
Grammar is the rules of how words are arranged into sentences. Without the knowledge of grammar one cannot produce sentences grammatically. If one makes a sentence whichÂ is not grammatically arranged, then that sentence cannot be said grammatical though perhaps it is still meaningful. Therefore, a sentenceÂ shouldÂ be grammatically correct and meaningfully acceptable. This study deals with the ability of the freshmen of the English Study Program on using English grammar in academic year 2019/2020. They are first given the pretest, and after studying for one semester they are given the posttest in order to see if there is significant difference from the pretest to posttest. It is expected that the learning-teaching process for one semester will give significant impact on the learning achievement. Based on the result of analysis of the test both in the pretest and posttest, it is found out that there found no difference between the result of the pretest and that of posttest. It is indicated by the mean score of the pretest 9.04 and that of posttest only 9.00. Therefore, it can be concluded that their ability on using English grammar is far below the average as the percentage of correct answer only 30.10% both in the pretest and posttest. Â Of the 17 topics covering the 30 test items both in the pretest and posttest, only 5 (five) items are correctly answered by more than 10 students within the percentage of 44% - 68%. On the whole,. Their ability on using English grammar is far below average.